Identification and Categorization of Volatile Sulfur Flavor Compounds in Roasted Malts and Barley. (2nd January 2023) - Parr, Hebe; Bolat, Irina; Cook, David
Abstract: We report for the first time the application of HS-SPME-GC coupled with sulfur-specific pulsed flame photometric detection to sensitively analyze the volatile sulfur compounds (VSC's) present in drum roasted malt and barley samples typically used in brewing. Twenty-five VSC's were identified across a range of 9 roasted products produced from barley/malt. Thiophenes (n = 10) were a major class of heterocyclic sulfur compounds identified, along with thiazoles (n = 4), and thiofurans (n = 2). Quantitative (n = 18) and semi-quantitative (n = 6) data are reported for VSC's across this product range. Principal Component Analysis (PCA) of data clearly identified (PC1) that heterocyclic sulfur compounds were formed in products processed at high temperatures (>170 °C) under dry conditions (roasted barley, chocolate and black malts). Whereas compounds such as methyl dithiolane and methyl propyl sulfide were associated primarily with lower temperature finished products (crystal, amber and cara malts). Pathways for the generation of observed VSC's are considered alongside typical roasting conditions employed in the manufacture of these products. Concentrations of VSC's identified will certainly contribute characteristic aromas to the roasted products themselves. The transfer of VSC's from the grist into finished beer, and their sensory impact in a range of beer styles, remains to be determined. Supplemental data for this article is available online at https://doi.org/10.1080/03610470.2021.2003669 .